Search for a heavy Higgs boson decaying into a Z boson and another heavy Higgs boson in the ℓℓbb and ℓℓWW final states in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Napolitano, Fabrizio; et al. (The European physical journal. C, Particles and fields, 2021)
A search for a heavy neutral Higgs boson, A, decaying into a Z boson and another heavy Higgs boson, H, is performed using a data sample corresponding to an integrated luminosity of 139 fb- from proton-proton collisions at √s=13 TeV recorded by the ATLAS detector at the LHC. The search considers the Z boson decaying into electrons or muons and the H boson into a pair of b-quarks or W bosons. The mass range considered is 230-800 GeV for the A boson and 130-700 GeV for the H boson.
Gesehen am 25.08.2021
Im Titel steht der Buchstabe s unter dem Wurzelsymbol